First records of occurrence and nesting of three bird species at Isla del Coco, Costa Rica - Acevedo-Gutiérrez, Alejandro (1994)
From February to August 1993 and from November 1993 to February 1994 seabird occurrence around Isla del Coco (OS030'N, 87°03'W), Costa Rica, was recorded as part of a larger field study on dolphin ecology. This note reports the first known records of Diomedea irrorata and Creagrus frcatus, and nesting of Sula dactylatra at Isla del Coco.